The Influence Of Content Marketing, On Purchase Decisions With Product Quality As A Mediation Variable And Brand Trust As A Moderating Variable On Pond's Facial Wash Products - Rahayu, Trio; Alfauzi, Asep Irpan; Ramadhan, Gilang; Rouf, Abdul; Saputra, Wishnu Anugrah Wahyu (Talent: Journal of Economics and Business, 2024)
The purpose of this study is to determine the influence of marketing content variables The influence of content marketing, on purchase decisions with product quality as a mediating variable and brand trust as a moderating variable on Pond's Facial Wash products at Pelita Bangsa University. By using quantitative methods, sampling methods and the population used are all students of Universitas Pelita Bangsa who use Pond's products. Meanwhile, the type and source of data used is primary data, namely data collected and processed by themselves obtained from the results of the distribution of questionnaires with a total of 105 respondents. Data analysis using SmartPLS3 (Partial Least Square). The results of this study. Content marketing has a positive but insignificant effect on purchase decisions, and variable  Brand Trus has a positive effect on purchase decisions , variables  Product quality has a positive effect on purchase decisions, variables  Content marketing have a positive effect on brand marketing,  Content Marketing has a positive effect on Product Quality, and Product Quality variables have a positive effect on purchase decisions.  This identifies that the existence of Product Quality, brand trus can influence consumer purchasing decisions so as to cause purchases of pond's products to increase.